Alih Kode dan Campur Kode oleh Pegawai Aerotravel di Denpasar - Novi Prasanthi, Ni Putu; Andry Anita Dewi, Ni Made; Yuliani Giri, Ni Luh Kade (Humanis; Vol 22 No 3 (2018)DO - 10.24843/JH.2018.v22.i03.p39, 2018)
This research aims to identify types and causes of code switching and code mixing that are applied  at Aerotravel Denpasar. This research is analyzed with “Agih and Padan” method in two different languages , Japan and Indonesian. On each of the language, it’s connected therefore found type and cause of factor code switching and code mixing. The theories used are code switching (Wardhaugh, 2006), code mixing (Hoffman, 1991) , and cause code mixing factor (Weinrich, 1979). From 20 data that is analyzed at Aerotravel, it resulted 6 type switching code: 1 methaporical code switching, 5 situational code switching. In addition there are 14 data of switching code consists of 10 lexical code mixing in lexical, 3 phonologic code mixing, and 1 sentence code mixing. The cause factors of switching codes are, topic, solidarity with communicator, social art distance, and motivation. The cause factor of code mixing are low frequency of word, need for synonym, social value, familiarity with another culture, and sufficiency differentiated. This research concludes that the situational code switching is the most used in code switching. Education background is the cause of code mixing existence.